Mathematical chemistry and chemoinformatics : structure generation, elucidation, and quantitative structure-property relationships - Kerber, Adalbert; Laue, Reinhard; Meringer, Markus; Rücker, Christoph; Schymanski, Emma, 1980- (Walter de Gruyter GmbH & Co., KG, 2014)
This work provides an introduction to mathematical modeling of molecules and its applications (structure generation, elucidation, evaluation; QSAR/QSPR etc.). It contains exercises and explanations of software packages in chemoinformatics that can be used directly via an online login code. It is aimed at users of structure generation and corresponding methods, but also for teaching and learning chemoinformatics and for software designers.